2019
DOI: 10.1016/j.tcs.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Displaying trees across two phylogenetic networks

Abstract: Phylogenetic networks are a generalization of phylogenetic trees to leaf-labeled directed acyclic graphs that represent ancestral relationships between species whose past includes non-tree-like events such as hybridization and horizontal gene transfer. Indeed, each phylogenetic network embeds a collection of phylogenetic trees. Referring to the collection of trees that a given phylogenetic network N embeds as the display set of N , several questions in the context of the display set of N have recently been ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, it would be interesting to explore quantum-classical hybrid approaches, as discussed in [1]. An immediate next step could be the development of a QUBO for problems that are closely related to Tree Containment such as the problem of deciding if a given phylogenetic network contains a given phylogenetic tree as a so-called base tree, or the problem of deciding if two phylogenetic networks display the same set of phylogenetic trees [3,13,18]. How different are QUBO formulations for these problems from the QUBO presented in this paper?…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it would be interesting to explore quantum-classical hybrid approaches, as discussed in [1]. An immediate next step could be the development of a QUBO for problems that are closely related to Tree Containment such as the problem of deciding if a given phylogenetic network contains a given phylogenetic tree as a so-called base tree, or the problem of deciding if two phylogenetic networks display the same set of phylogenetic trees [3,13,18]. How different are QUBO formulations for these problems from the QUBO presented in this paper?…”
Section: Discussionmentioning
confidence: 99%
“…or it has a cherry in {{x, 0 }, {x, 1 }, {x, 2 }}. Both cases contradict the restriction of T in (8) when considering E ; thereby implying that (u, w) is a shortcut and u lies on the tree path from p 2 to p 1 . Now, let E 1 be an embedding of a phylogenetic X-tree T that uses…”
Section: 81mentioning
confidence: 95%
“…To complete the proof, we establish a reduction from the Π P 2 -complete problem Display-Set-Containment to Non-Essential-Arc. The reduction has a similar flavor to that used in [8,Theorem 4.5]. Throughout the remainder of the proof, we sometimes label internal vertices of a phylogenetic network.…”
Section: Display-set-containmentmentioning
confidence: 99%
“…In particular, we consider the problem of deciding whether or not two given phylogenetic networks embed the same set of phylogenetic trees. Called Display-Set-Equivalence, we recently showed that, in general, this problem is Π P 2complete [5], that is, complete for the second-level of the polynomial hierarchy. Problems on the second level of the hierarchy are computationally more difficult than problems on the first level which include all NP-and co-NPcomplete problems.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown in [5] that, in general, Display-Set-Equivalence is Π P 2complete. In contrast, the main result of this paper shows that this decision problem is solvable in polynomial time if N is normal and N is tree-child.…”
Section: Introductionmentioning
confidence: 99%